Representasi Relasi Manusia Dan Alam Dalam Cerita Pendek “Asa Dan Hutan Kalimantan” Karya Yosimar Akbar - Aghist Muflihah Zahra; Melinda Febriani; Ian Wahyuni (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
This research uses a type of qualitative research using an ecocritical perspective. This research aims to identify forms of environmental wisdom and ecological criticism in the short story Asa and Hutan Kaimantan using Norman Fairclough's theory of critical discourse analysis, namely, identity, representation and relationships. The data in this research are several texts contained in short stories, while the data source in this research is the primary data source in the form of the short story "Asa and the Kalimantan Forest by Yosimar Akbar. Data collection techniques are carried out using reading and note-taking techniques, while data analysis techniques are carried out through the stages of identification, classification, interpretation and drawing conclusions. The results of the research show that in the short story "Asa and the Kalimantan Forest by Yosimar Akbar, a representation of environmental wisdom was found in the form of a responsible attitude towards nature. Apart from that, in the text of the novel there is also ecological criticism in the form of ecological criticism of individuals who throw away cigarette butts without extinguishing them in the forest environment and of groups of poachers who hunt orangutans.